(untitled) (Coordinates of Public Administration, 2026)
The article examines the activities of transnational corporations of the defense-industrial complex as specific non-state actors of international relations, combining arms production, export, service, technological partnership, participation in state procurement and the formation of expert-political discourse. It is shown that the modern arms market has a dual character: it is transnational in terms of cooperation chains, but at the same time remains deeply state-centric in terms of sources of demand, control regimes and political weight of contracts. According to SIPRI, military spending in the world in 2025 reached 2.887 trillion, and the income of the 100 largest companies from the sale of arms and military services in 2024 amounted to 679 billion; At the same time, the volume of international transfers of major weapons in 2021–2025 was 9.2% higher than in 2016–2020. We can conclude that the influence of defense TNCs should be analyzed not as an accidental side effect of the market, but as a structural element of modern security policy. Particular attention is paid to the USA as the state in which this influence is most fully documented. The American case combines at least four channels of influence: market concentration, lobbying and political contributions, a «revolving door» between government and business, and the inclusion of arms sales in official foreign and industrial policy instruments. A summary based on the OpenSecrets database shows that the military industry spent more than 139 million on lobbying in 2023 alone, maintained 904 lobbyists, and over the decade directed almost 1.3 billion to lobbying activities; At the same time, fifteen years of market consolidation have led to the dependence of the state on a very narrow circle of contractors. The US federal government itself describes Foreign Military Sales as a fundamental instrument of foreign policy, and the 2026 executive act directly obliges to use arms transfers to expand strategically relevant production capacities in the US. In a comparative dimension, the author’s position of the article is that the policy of almost every state in the world is indeed changing under the influence of defense TNCs, but not to the same extent and not by the same mechanisms. In liberal democracies, legal channels of influence prevail – lobbying, analytical networks, budgetary pressure and geographical dispersion of production. Within NATO, corporate influence is more often embedded in a common industrial policy, standardization, long-term framework purchases and cooperation with states. In import-dependent states, the main mechanism is dependence on maintenance, modernization and political guarantees of access to ammunition and spare parts. In state-capitalist systems, the state often dominates corporations, but there too another form of fusion emerges-bureaucratic-industrial. Thus, defense corporations do not «abolish» sovereignty, but redistribute power within it, shifting policy toward long-term defense commitments, export diplomacy, and industrial patronage.